Insights into the yield enhancement and ion emission process in metal‐assisted SIMS. (5th June 2012) - Nittler, L.; Delcorte, A.; Bertrand, P.; Migeon, H.‐N.
<x xml:space="preserve">Abstract</x> Although nowadays the use of cluster ion sources seems to enhance the secondary ion emission for nearly all materials, the technique of metal‐assisted SIMS can still give further insights in the secondary ion emission process. In this study, the metallization for static SIMS analysis was performed in situ. The combination of a detailed morphology study by SEM, TEM and the secondary yield enhancements in time‐of‐flight SIMS allows to develop a model explaining the secondary yield enhancement in metal‐assisted SIMS. Copyright © 2012 John Wiley & Sons, Ltd.